Wacana Kritis Normal Fairclough Berita Media Massa Daring: Jepang Buang Limbah Nuklir - Khosnol Khotimah; Khusnul Khotimah (Universitas Sebelas Maret, 2024)
This research aims to critically explain an event, analyze discourse, and identify crucial elements in the event of Japan disposing nuclear waste into the sea. The data source for this study comprises news articles on Japan's disposal of nuclear waste from five different online mass media outlets: CNN Indonesia, Detik.com, Liputan6.com, Kompas.com, and CNBC Indonesia. The research employs a qualitative descriptive research method using observation and note-taking techniques. The news articles are analyzed using Norman Fairclough's AWK, which includes three dimensions: microstructural, mesostructural, and macrostructural. The analysis results indicate that in the news articles, there is a microstructural dimension reflected in the use of almost identical vocabulary, specifically